Urotechnology: a new interdisciplinary platform for promoting and managing of technical innovations in urology - Miernik, A.; Becker, C.; Wullich, Bernd; Schoenthaler, M.; Arnolds, B. J.; Wetterauer, U. (Urologe, 2015)
The innovative power in medical engineering and technology development requires a close cooperation between universities and non-university research institutions and a collaboration with industrial partners. German knowledge in the fields of video and micro-optics, microsystem technology and of informational technology and software applications seem to be highly competitive at international level. Germany's previous leadership in the development of technical equipment will be challenged by today's requirements and difficulties in medical engineering. Research and expenses demands for the development of novel medical instruments, products and applications will increase continuously. Transparency and coordinated collaboration between universities and industrial partners will contribute to a substantial improvement in surgical therapy. Medical technology of the future, including urotechnology, requires professional structures and coordination and will have to be based on evidence.
EVALuna2:16333